Wages as an element of the incentive system for employees of construction enterprises - Dropa, I. (Ways to Improve Construction Efficiency, 2022)
The article is devoted to substantiating modern approaches to the formation and regulation of wages in construction enterprises of Ukraine. Special attention is given to the need to ensure work quality and to strengthen the competitiveness of enterprises in the labor market. The purpose of the article is to identify the features and systemic problems of wage organization in construction enterprises and to develop practical recommendations for strengthening its motivational role. The analysis of current trends has shown that wages in the construction sector have long failed to fully perform their reproductive and stimulating functions due to low basic rates, widespread informal payments, untimely settlements, and the migration of qualified personnel. To integrate wage policy into the business strategy of construction enterprises, a three-level model is proposed that transforms the wage fund from a passive cost item into an active instrument of strategic human capital management. The model provides for the inclusion of automatic indexation in collective agreements, complemented by digital monitoring and enhanced employer accountability, which guarantees the preservation of employees’ purchasing power. It also covers incentive mechanisms through industry-wide compensation packages, transparent rules of remuneration, and a combination of individual and collective bonuses. The final element is strategic integration, in which the reward system is aligned with business model objectives, while career tracks with automatic salary increases after attestation or certification are combined with the digitalization of labor and quality accounting. Such an approach makes it possible to transform the wage system into an effective tool for performance management. Implementation of the model creates conditions for preserving employees’ real purchasing power, stimulating labor productivity and quality of work, and reducing staff turnover through stable and predictable rewards. Altogether, this forms a basis for improving the competitiveness of construction enterprises and enhancing their investment attractiveness in the long term.